Outages in sovereign bond markets - Mark Kerssenfischer; Caspar Helmus (European Central Bank (ECB), 2024)
We use outages as natural experiments to study sovereign bond market functioning. When the euro area futures market goes down, trading activity on the cash market declines, liquidity evaporates, and transaction prices deviate from fundamental values. Tracing back this macro-level market breakdown to the micro-level, we show that particularly dealers withdraw from the cash market during outages. While most of their remaining trades remain fairly priced, dealer's capacity to intermediate trades on the cash market is reduced, forcing more clients to trade directly with each other, leading to substantial mispricing. Lastly, outages on cash trading venues barely affect the futures market, suggesting that price formation and liquidity provision is a one-way street, and outages on the US and euro area futures market barely affect each other, in stark contrast to the significant price spillovers. Our results reveal the trade-offs between a (de)centralized market structure, they support cross-asset learning models to explain the link between liquidity and arbitrage, and they demonstrate how financial intermediaries can impose important limits to arbitrage.
Keywords: G12; G14; G23; 330; Yield curve; market microstructure; natural experiment